Sex-related head size and shape dimorphism in Mapaná snakes (Bothrops asper) kept in captivity (2013)
ABSTRACT: sexual size dimorphism in snakes is generally well documented, however, sexual shape dimorphism has been poorly studied. As snakes are considered gape-limited predators, identifying patterns of sexual size and head shape dimorphism can help elucidate the life history of these organisms. Objective: to detect differences between sexes regarding head size and shape dimorphism of Mapaná snakes (Bothrops asper) maintained in captivity under the same diet in order to determine if it has a plastic or genetic origin. Methods: geometric morphometrics were used to quantify the head size and shape of male and female Mapaná snakes. Results: our results suggest that head shape is sexually dimorphic, being relatively wider in females compared to males. In both sexes head shape also varied with snout-vent length (SVL), growing wider as body size increases. Head size was also sexually dimorphic, with female head being larger than that of males of the same body length. Head size also increased with SVL. However, female head size increased disproportionally faster when compared to males. Conclusions: evidence of sexual differences in head size and shape of Mapaná snakes raised under the same diet was found. These findings suggest that sexual head size and shape dimorphism is not a plastic response given that both sexes were maintained under similar conditions, which suggests a strong genetic basis. Sexual shape dimorphism is also being mediated by stronger phenotypic changes of females while males seem to have a more constrained phenotypic head development.